El discurso propagandístico del partido Movimiento Popular Democrático (MPD) en la ciudad de Quito en el período 2009-2013 - Zambrano Cortéz, Jenny Susana (2015)
The present work realizes an analysis of the propagandistic discourse of the Partido Movimiento Popular Democrático (Popular Democratic Movement Party, “MPD”) emitted in the city of Quito from 2009-2013. The first chapter undertakes a conceptual approximation regarding the terms and categories concerning democracy, political communication, and the political party propaganda system. The second chapter identifies the elements and political context in which the MPD first originated and later disappeared. Some of the themes developed in this section include: the return of democracy to Ecuador; the political party system; the Government Program; the legal statutes (i.e. the Constitution); the Declaration of Political and Ideological Principles; and the systemization of media-use by the MPD in the propagandistic discourse. The third chapter is dedicated to an analysis of the content of MPD’s propagandistic discourse. In order to do so, a theoretical approximation of the following elements is realized: iconography; color and semantics; and a qualitative investigation regarding material content. The structure, characterization of unit analysis, and results of a focus group study are also discussed in this section. The final section present the conclusions and recommendations stemming from the iconographic, chromatic, and semantic composition, as well as the perception that the citizenry retains with regards to the MPD, its discourse, and party members.